Circuitos elétricos : uma sequência didática para o ensino médio - Marques, Izuleide Morais Rosa (2021)
This work was born from the need to present active methodologies that seek to assist physics teachers in the classroom, promoting an experimental and investigative character, emphasizing the student's role. Therefore, we present a proposal for teachers who work with the third year of high school, with the content of electrodynamics. The main objective of this work was to produce a didactic sequence on electrical circuits, through the development of experimental kits related to basic electronics topics. In this sense, the methodology used prioritized the student's involvement in the construction of their learning, through a didactic sequence that included research, experimentation and active development in the teaching-learning process, making a more attractive and reflective environment in the teaching of physics. After the application of this product, it was noticed the importance of combining the physical concepts discussed in the classroom with the experimental activities, this practice allowed to achieve good results, making students subject to the action and not only supporting learning.